2014
DOI: 10.1194/jlr.m045898
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of the plasma triglyceride response to an n-3 polyunsaturated fatty acid supplementation

Abstract: Numerous meta-analyses have demonstrated that the long-chain n-3 PUFAs (LC n-3 PUFAs; EPA and DHA) signifi cantly reduce plasma TG levels in a dose-dependent manner, with the TG lowering being proportional to baseline levels ( 1, 2 ). In trials of subjects with high TG levels, n-3 PUFAs in dosages of 3.4-4.0 g/day decreased TG levels by 16% to 45% ( 1 ). However, there is well-recognized heterogeneity in the plasma TG response to LC n-3 PUFA supplementation ( 3 ): for example, 31% of all volunteers from the Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 31 publications
5
76
0
2
Order By: Relevance
“…Our fi ndings of variable increases in n-3 plasma phospholipid fatty acid concentratations following supplementation are consistent with accumulating evidence for substantial variability in responses in circulating levels of n-3 PUFA following dietary supplementation ( 15,22,23 ). There is increasing interest in how such variation might be a determinant of the impact of n-3 PUFA on cardiovascular risk factors and clinical outcomes ( 24 ) because incorporation of n-3 PUFA into phospholipids could infl uence physical properties of cellular membranes and associated protein (e.g., ion channel) functions.…”
Section: Discussionsupporting
confidence: 62%
“…Our fi ndings of variable increases in n-3 plasma phospholipid fatty acid concentratations following supplementation are consistent with accumulating evidence for substantial variability in responses in circulating levels of n-3 PUFA following dietary supplementation ( 15,22,23 ). There is increasing interest in how such variation might be a determinant of the impact of n-3 PUFA on cardiovascular risk factors and clinical outcomes ( 24 ) because incorporation of n-3 PUFA into phospholipids could infl uence physical properties of cellular membranes and associated protein (e.g., ion channel) functions.…”
Section: Discussionsupporting
confidence: 62%
“…Conversely, subjects with higher GRS for glucose disorders had greater increases in fasting glucose when consuming a high-fat diet [32]. Moreover, a GRS built from genes identified by genome-wide association studies, partially explained the variation in triglyceride changes in response to omega-3 fatty acid supplementation [33]. …”
Section: Genetic Background and Nutritional Prescriptionsmentioning
confidence: 99%
“…The whole study design and diets have been previously reported [10]. Briefly, subjects followed a run-in period of 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Methods to measure plasma lipids have previously been detailed [10]. Briefly, blood samples were collected after a 12-hour overnight fast and 48-hour alcohol abstinence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation